2017
DOI: 10.1039/c7nr01482a
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterning of GeTe phase change films via heated-probe lithography

Abstract: The crystallization of amorphous germanium telluride (GeTe) thin films is controlled with nanoscale resolution using the heat from a thermal AFM probe. The dramatic differences between the amorphous and crystalline GeTe phases yield embedded nanoscale features with strong topographic, electronic, and optical contrast. The flexibility of scanning probe lithography enables the width and depth of the features, as well as the extent of their crystallization, to be controlled by varying probe temperature and write … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…6f. As expected, electrical characterization of the patterned nanostructures showed that the crystallized nanostructures became electrically conducting, in contrast to the non-conducting amorphous GeTe 98 .…”
Section: Local Crystallizationsupporting
confidence: 76%
See 2 more Smart Citations
“…6f. As expected, electrical characterization of the patterned nanostructures showed that the crystallized nanostructures became electrically conducting, in contrast to the non-conducting amorphous GeTe 98 .…”
Section: Local Crystallizationsupporting
confidence: 76%
“…c Amorphization by short heating and fast subsequent quenching to obtain a less ordered phase 96,97 . d Local crystallization of an amorphous material 21,[98][99][100][101][102] . e Heat-assisted local alignment of magnetic dipoles [104][105][106][107] Organic semiconductors…”
Section: Chemical Conversion Deprotection Of Functional Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the technology was initially developed for data storage, t-SPL has become an emerging lithography method for nanopatterning of temperature-sensitive and functional materials, such as polymers, 2,3 graphene oxide, 4 molecular glasses, 5 metal alloys, 6 and semiconductors. 79 Closed-loop lithography, a key feature of t-SPL, enables thermal patterning of a substrate material with the tip being heated and in situ recording of the surface topography with the tip being at room temperature. This enables rapid prototyping of three-dimensional (3D) patterns into temperature-sensitive resists, 2,3 which can subsequently be transferred into silicon or used for lift-off.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 t-SPL is not limited to organic materials and has been applied on GeTe phase change materials to create crystalline, electrically conductive, and optically absorptive nanoscale patterns from an amorphous, transparent, and electrically insulating substrate. 9 In comparison to laser-assisted nanoimprint lithography 13 or ultrafast thermal nanoimprint lithography, 14 t-SPL is a digital patterning technique which does not require a mask.…”
Section: Introductionmentioning
confidence: 99%